SOME PHYSIOLOGICAL AND BIOCHEMICAL RESPONSES TO NICKEL IN SALICYLIC ACID APLIED CHICKPEA (CICER ARIETINUM L.) SEEDLINGS - Canakci, Songul; Dursun, Bahar (Akademiai Kiado Rt, 2011)
The present study examined the effects of salicylic acid pre-application on the responses of seven-day-old chickpea (Cicer arietinum L.) seedlings to nickel. For this purpose, the plants were treated with 1 mM salicylic acid solution for 6 and 10 hours and then treated with 0.75, 1.5 and 3 mM nickel solutions for 48 hours hydroponically. Following the treatment, changes in seedling length, seedling fresh weight and leaf dry weight (after 10 hours), as well as MDA, proline, protein and pigment contents (after 6 and 10 hours) were examined. Salicylic acid pre-application was found to significantly alleviate the typical harmful effects caused by nickel and 3 mM nickel concentration in particular, on the parameters associated with toxic stress. However, pre-application of salicylic acid for 6 and 10 hours without nickel treatment did not produce any stimulatory or inhibitory effect on the seedlings as compared to the controls.
Keywords: Cicer arietinum; salicylic acid; nickel; toxicity